Mengucapkan Salam dan Selamat Natal dalam Pandangan Hukum Islam (Analisis Terhadap Penafsiran Surat al-Nisa’ ayat 86 dan Maryam ayat 33) - Willya, Evra (Alhurriyah, 2009)
Greeting of peace and merry Christmas would be contradicted when it involved with the faith. As a consequence, there would be an instruction to ban it. In contrast, it would be not in the same way when it related with the relationship context among human being as a fellow religion in a society. Greeting of merry Christmas could be not understood as a statement accepting and agreeing the Christian believe. The greeting regarded to be allowed as long as it regards as an expression of peace and appreciation in the society as a fellow religion. This is the same way when we come to the celebration for their great day. If a person believes that his faith would be not change, then he is allowed to come to the celebration. On the other hand, if the person afraid of changing his faith, then it would be forbidden to come to their celebration.